Variability Studies in Brinjal (Solanum melongena L.) - Shilpa, B. M.; Dheware, R. M.; Kolekar, R. B. (International Journal of Bio-resource and Stress Management, 2018)
The present investigation was carried out at Instructional-Cum-Research Farm, Department of Horticulture, College of Agriculture, Latur during Kharif season, 2016-17;to study the variabilities in brinjal. To conduct the study eighteen genotypesof brinjal viz., Poiyoor, Nagarkoil, Chettipulam, Vengaloor, Br.CVK (spineless), Erangere, Rampur Local, Panrutti, Rayadurga Local, Gulabi, Pusa Purple round, Arka Keshav, Malapura Local, Pune Kateri, Padhukottai, Kateri Wangi, Br. CVK (spine) and Vettai Mangalam wereevaluated for 19 quantitative characters. A wide range of variations were observed among different genotypes for all growth, yield and quality characters. The phenotypic coefficient of variation was higher than genotypic coefficient of variation for all the traits. High (>20%) genotypic coefficient of variation (GCV) and phenotypic coefficient variation (PCV) were observed for fruit dry matter %, fruit yield plant-1, weight of fruits, leaf petiole length, fruit yield hectare-1, fruit yield plot-1, plant height and days required for first flowering. High heritability (>60%) coupled with high genetic advance as percent over mean (>20%) were recorded for the characters viz., plant height, leaf petiole length, days required for first flowering, fruit pedicel length, fruit length, fruit diameter, number of fruits plant-1, weight of fruits, fruit yield plant-1, fruit yield plot-1, fruit yield hectare-1, fruit dry matter % and fruit protein %. The additive component is predominant for the above characters.